An ATP-binding cassette transporter G2 (CgABCG2) regulates the haemocyte proliferation by modulating the G1/S phase transition of cell cycle in oyster Crassostrea gigas. Issue 136 (May 2023) - Yu, Simiao; Qiao, Xue; Yang, Ying; Gu, Xiaoyu; Sun, Wending; Liu, Xiyang; Zhang, Dan; Wang, Lingling; Song, Linsheng
Abstract: ATP-binding cassette transporter G2 (ABCG2) is a half-transporter of the G subfamily in ATP-binding cassette transporters (ABC transporter), which is involved in the regulation of multidrug-resistant, cell cycle, and cell proliferation. In the present study, a homologue of ABCG2 (named as Cg ABCG2) with the conserved AAA domain and ABC2 membrane domain was identified from the Pacific oyster Crassostrea gigas . The open reading frame (ORF) of Cg ABCG2 was of 1956 bp encoding a predicted polypeptide of 652 amino acids, which shared 56.7%–65.7% sequence similarities with previously identified ABCG2s from other animals. The mRNA transcripts of Cg ABCG2 were detected in all the tested tissues with higher expression levels in gonad and haemocytes (19.31-fold and 11.23-fold of that in adductor muscle respectively, p  < 0.05). Cg ABCG2 was mainly distributed on the cell membrane of the haemocytes with a partial distribution in the cytoplasm and nucleus. After Vibrio splendidus stimulation, the mRNA expression level of Cg ABCG2 in haemocytes was significantly up-regulated at 3 h and 6 h, which was 5.22-fold and 8.60-fold ( p  < 0.05) of that in control, respectively. After the expression of Cg ABCG2 was interfered by RNAi, the number of cells with EdU positive signals was reduced in both haemocytes and the potential hematopoietic sites. And the mRNA expression level of Cg PCNA, Cg GATA3, Cg Runx, Cg SCL and Cg C-kit decreased significantly ( p  < 0.05), which were about 0.66-, 0.37-, 0.32-, 0.50-, and 0.50-fold of that in the negative control group, respectively. While the mRNA expression level of Cg CDK2 increased significantly (1.84-fold to that in control, p  < 0.05) and that of stem cell-related factor Cg SOX2 did not change significantly in the si- Cg ABCG2 oysters. Moreover, the cell cycle of haemocytes was detected by flow cytometry, which was arrested at G0/G1 phase in the si- Cg ABCG2 oysters. All the results collectively suggested that Cg ABCG2 might involve the proliferation of haemocytes by regulating the expression of haematopoiesis related transcription factors and the G1/S phase transition of the cell cycle in oyster C. gigas . Highlights: A homologue of ATP-binding cassette transporter G2 (ABCG2) was identified in Pacific oyster C. gigas. The mRNA expression of Cg ABCG2 in haemocytes was significantly up-regulated post V. splendidus stimulation. The inhibition of Cg ABCG2 reduced the expressions of haematopoiesis related transcription factors. The cell cycle was arrested at G0/G1 phase and the cell proliferation was reduced in the si- Cg ABCG2 oysters.